A trajetória das paixões em relatos de professores sobre violência intrafamiliar sofrida por discentes - Menezes, Fabiana Lisboa Ramos (2024)
Intrafamily violence is a factor that makes children and adolescents even more vulnerable. It is in this sense that this work is based on teacher reports that expose one of the many situations of violence that are perceived at school. Given the importance of family and school in the development and protection of these subjects in training, this study intends to analyze how teachers, in the audience, are emotionally affected by their students' confidences about cases of intra-family violence. The objective is to investigate the teaching passions inscribed in the reports from the perspective of the Trajectory of passions, following the steps presented by the analytical device: availability, identification, awakening of passion, change of judgment, and action. This procedure has as its theoretical reference the studies developed by Figueiredo (2018, 2019, 2020) based on the work Rhetoric by Aristotle (2015), studies on New Rhetoric by Perelman and Olbrecht-Tyteca (2014) and Meyer (2000, 2007), about affectivity in the context of family and education, with Spinoza (2009) and the power relations that generate vulnerability, from the perspective of Butler (2017), Foucault (1995) and Feito (2007). As objects of analysis, the reports were requested through questionnaires in a meeting of teachers, who wrote about their experiences interacting with students. The corpus was obtained by applying a semi-structured questionnaire with dichotomous questions and requesting an experience report. The results showed that the passion of trust is the first to be awakened, as the interaction between student and teacher regarding the case of violence depends on this, which arouses indignation as it is revealed. Indignation and fear are the most recurrent passions in the reports. This conclusion made it possible to propose the notion of impeding passions, which are the passions that prevent the intended action and favor deliberations based on pity, fear, and importance. We observed that it was possible to identify the passions experienced by teachers and understand them in the persuasive path, within the scope of the Trajectory of passions and in a social context that goes beyond education, which is the protection of life.